2018
DOI: 10.1002/jsc.2228
|View full text |Cite
|
Sign up to set email alerts
|

After Brexit: Rethinking the structure of the UK economy and its branding strategies

Abstract: Brexit is currently making the economic climate uncertain. It will have an impact on the economic health of the UK economy and its products may suffer as consequence. It presents conditions for engendering both the positive and negative features of a falling currency. Associated with Brexit is the possibility of negative customer brand perceptions, a result of the UK country of origin effect. This raises the issue of considering alternative strategic routes to growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…However, the inclusion of implicit and explicit British provenance information on product labelling and packaging design is evident, with the practice becoming particularly prominent during the Brexit debate (Ardley, 2018) and the COVID-19 pandemic (Bentall et al, 2021). Even before these periods, a renewed consumer interest in the Made in Britain label was observed and considered a prominent marketing strategy (Comunian and England, 2018), with domestic retailers launching their own British-made product ranges.…”
Section: The Coo Effectmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the inclusion of implicit and explicit British provenance information on product labelling and packaging design is evident, with the practice becoming particularly prominent during the Brexit debate (Ardley, 2018) and the COVID-19 pandemic (Bentall et al, 2021). Even before these periods, a renewed consumer interest in the Made in Britain label was observed and considered a prominent marketing strategy (Comunian and England, 2018), with domestic retailers launching their own British-made product ranges.…”
Section: The Coo Effectmentioning
confidence: 99%
“…Even before these periods, a renewed consumer interest in the Made in Britain label was observed and considered a prominent marketing strategy (Comunian and England, 2018), with domestic retailers launching their own British-made product ranges. Within the last few decades, British brands generally have become synonymous with creativity, freedom and rebelliousness, supported by a loyal consumer base (Ardley, 2018). Groves (2001) found that a British mark shares positive synonymous product attributes such as authenticity and quality within the FMCG sector particularly, with Benton et al (2017) reporting an increase in domestic consumers preferring to buy British.…”
Section: The Coo Effectmentioning
confidence: 99%
See 3 more Smart Citations